2009
DOI: 10.1126/science.1178722
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Accurate Simulation of a Prototypical Surface Reaction: H 2 Dissociation on Cu(111)

Abstract: Methods for accurately computing the interaction of molecules with metal surfaces are critical to understanding and thereby improving heterogeneous catalysis. We introduce an implementation of the specific reaction parameter (SRP) approach to density functional theory (DFT) that carries the method forward from a semiquantitative to a quantitative description of the molecule-surface interaction. Dynamics calculations on reactive scattering of hydrogen from the copper (111) surface using an SRP-DFT potential ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
600
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 339 publications
(633 citation statements)
references
References 37 publications
32
600
1
Order By: Relevance
“…We study the (111) surface because an accurate 6D PES for this surface is already available in the literature. 35 Also in view of the rather similar experimental results obtained for the (100) and (110) surfaces, no major discrepancies would be expected between low-Miller-indices Cu surfaces. Keeping in mind that we perform our study for the (111) surface whereas the experiments we compare to were done for the (100) surface, we do not attempt a quantitative comparison with experiment.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…We study the (111) surface because an accurate 6D PES for this surface is already available in the literature. 35 Also in view of the rather similar experimental results obtained for the (100) and (110) surfaces, no major discrepancies would be expected between low-Miller-indices Cu surfaces. Keeping in mind that we perform our study for the (111) surface whereas the experiments we compare to were done for the (100) surface, we do not attempt a quantitative comparison with experiment.…”
Section: Introductionmentioning
confidence: 62%
“…In performing the DFT/GGA calculations, we have used the exchange-correlation functional PW91, 51 which yields a semi-quantitative description of the H 2 /Cu(111) system. 36 We also show results obtained with the specific reaction parameter (SRP) functional developed by Díaz et al, 35 which has been shown to give chemical accuracy for a significant number of H 2 /Cu(111) observables.…”
Section: Methodsmentioning
confidence: 78%
See 1 more Smart Citation
“…In contrast, the relevance of this dissipation channel in gas-surface interactions that involve energies up to a few eV is not so clear. It depends not only on the specific system, but also on the elementary process considered, as shown by different studies on scattering [5][6][7][8][9][10][11][12] and adsorption [6,[13][14][15][16][17][18][19][20][21][22][23][24][25][26] of atoms and molecules on surfaces. Low-energy e-h pair excitations have been detected as chemicurrents on Schottky diode devices during the chemisorption of atomic and molecular species on metals [13][14][15].…”
mentioning
confidence: 99%
“…Six-dimensional quantum dynamics has already become a standard tool to study diatomic molecule/surface interactions at low incidence energy(<2 eV), from reactive scattering [20][21][22][23][24] to molecular diffraction [24][25][26]. However, its accuracy in reproducing experimental data, disregarding phonons * cristina.diaz@uam.es and electron-hole pair excitations effects, relies on the accuracy of the underlying potential energy surface (PES) on which the dynamics is carried out [23,27]. Thus the large progress made in the microscopic dynamics description of moleculesurface interaction processes has motivated, subsequently, the development of flexible and accurate methods to determine full-dimensional PESs.…”
Section: Introductionmentioning
confidence: 99%